Oral granuloma formation after injection of cosmetic filler - Quirino, Maria Rozeli de Souza; Neves, Ana Christina Claro; Campos, Márcia Sampaio; Brandão, Adriana Aigotti Haberbeck; Anbinder, Ana Lia [UNESP] (Elsevier, 2012)
The increased use of orofacial fillers in cosmetic procedures has led to new diagnostic challenges for dentists and oral pathologists. Here, we describe a case with multiple oral foreign body granulomas, which were formed after a polymethylmetacrylate injection for cosmetic purposes. © 2011 European Association for Cranio-Maxillo-Facial Surgery.
Keywords: Artecoll; Oral foreign body granuloma; Orofacial fillers; Polymethylmethacrylate; clonazepam; cosmetic; methacrylic acid; paroxetine; polymethylmetacrylic acid; simvastatin; triamcinolone acetonide; unclassified drug; adult; case report; clinical feature; corticosteroid therapy; drug withdrawal; echography; female; foreign body granuloma; gastritis; histopathology; human; human tissue; lip biopsy; medical history; mouth tumor; nuclear magnetic resonance imaging; oral foreign body granuloma; tooth implantation; treatment response; Biocompatible Materials; Cosmetic Techniques; Female; Follow-Up Studies; Foreign Bodies; Giant Cells; Granuloma, Foreign-Body; Humans; Macrophages; Middle Aged; Mouth Diseases; Polymethyl Methacrylate